Tri hita karana culture and organizational commitments moderate: effect of participation on budgetary slack - Sukayana, Gede Adi; Putri, I.G.A.M Asri Dwija (International research journal of management, IT and social sciences, 2019)
This research was conducted in order to obtain evidence of how the effect of budgetary participation on budgetary slack in Bali Provincial OPD with the tri hita karana culture and organizational commitment as a moderating variable. This research was conducted in 45 Regional Organizations in Bali Province. The research sample was determined by purposive sampling method and based on the specified criteria obtained a total sample of 203 respondents. Data collection is done using the questionnaire method. The hypothesis is tested using simple regression analysis techniques and the Moderating Regression Analysis. The results showed that budgetary participation had a positive effect on budgetary slack. The Tri Hita Karana culture shows that weakening the positive effect of budgetary participation on budgetary slack and organizational commitment shows that it weakens the positive effect of budgetary participation on budgetary slack.